The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/eji.200839103
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Treg by monocyte‐derived DC modulated by vitamin D3 or dexamethasone: Differential role for PD‐L1

Abstract: Specific therapy with modulated DC may restore immunological tolerance, thereby obviating the need for chronic immunosuppression in transplantation or autoimmunity. In this study we compared the tolerizing capacity of dexamethasone (Dex)-and 1a,25-dihydroxyvitamin D3 (VD3)-modulated DC. Treatment of monocytes with either VD3 or Dex resulted in DC with stable, semi-mature phenotypes compared with standard DC, with intermediate levels of co-stimulatory and MHC class II molecules, which remained unaltered after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
330
3
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(376 citation statements)
references
References 61 publications
21
330
3
17
Order By: Relevance
“…Our data point to the expansion of preexisting Tregs, rather than the conversion from naive CD4 + T cells, because 1,25D 3 -mDCs failed to reproduce the characteristic increase in Treg frequency in vitro following coculture with CD25-depleted CD4 + T cells. In contrast, different groups (11,12,53) (54). In addition to pointing to the expansion of Tregs, our data show that CD4 + CD25 + Tregs expanded in the presence of 1,25D 3 -mDCs featured elevated levels of regulatory mediators, such as IL-10, which might be relevant for their increased suppressive function in vivo.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Our data point to the expansion of preexisting Tregs, rather than the conversion from naive CD4 + T cells, because 1,25D 3 -mDCs failed to reproduce the characteristic increase in Treg frequency in vitro following coculture with CD25-depleted CD4 + T cells. In contrast, different groups (11,12,53) (54). In addition to pointing to the expansion of Tregs, our data show that CD4 + CD25 + Tregs expanded in the presence of 1,25D 3 -mDCs featured elevated levels of regulatory mediators, such as IL-10, which might be relevant for their increased suppressive function in vivo.…”
Section: Discussionmentioning
confidence: 55%
“…However, clinical applications of DC-based therapies in autoimmune disease intervention are hampered by the concern that iDCs will develop into immunostimulatory cells upon encountering inflammatory stimuli in vivo. In this sense, we (9,14,18) and other investigators (6,7,12) showed that mDCs differentiated and matured in vitro in the presence of the biologically active form of vitamin D, 1,25(OH) 2 D 3 , produced a stable phenotype, typically characterized by low levels of Ag-presenting and costimulatory molecules (MHCII, CD80, CD86), as well as a high ratio of PD-L1/CD86 and anti-inflammatory cytokines (IL-10, TGF-b). In this study, we further demonstrated the capacity of 1,25(OH) 2 D 3 to imprint a similar tolerogenic profile in mDCs derived from diabetes-prone mice and diabetes-resistant animals.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Both macrophages and T reg cells are implicated in the above studies. PD-L1 expression on dendritic cells (DCs) is required for the induction of T reg cells by vitamin D3, perhaps through reverse signaling by PD-L1 to DCs 80 . It is possible that the regulation of PD-1-PD-L1 signaling at discrete stages during the immune response could diminish immunotoxicity in individuals with cancer.…”
Section: Box 1 Adoptive T Cell Therapymentioning
confidence: 99%